Integer Linear Programming-Based Simultaneous Scheduling and Binding for SiLago Framework - Pudi, Dhilleswararao; Malviya, Shivam; Boppu, Srinivas; Yang, Yu; Hemani, Ahmed; Cenkeramaddi, Linga Reddy (IEEE access, 2024)
Coarse-Grained Reconfigurable Array (CGRA) architectures are potential high-performance and power-efficient platforms. However, mapping applications efficiently on CGRA, which includes scheduling and binding operations on functional units and variables on registers, is a daunting problem. SiLago is a recently developed VLSI design framework comprising two large-scale reconfigurable fabrics: Dynamically Reconfigurable Resource Array (DRRA) and Distributed Memory Architecture (DiMArch). It uses the Vesyla compiler to map applications on these fabrics. The present version of Vesyla executes binding and scheduling sequentially, with binding first, followed by scheduling. In this paper, we proposed an Integer Linear Programming (ILP)-based exact method to solve scheduling and binding simultaneously that delivers better solutions while mapping applications on these fabrics. The proposed ILP combines two objective functions, one for scheduling and one for binding, and both of these objective functions are coupled with weightage factors α and β so that the user can have the flexibility to prioritize either scheduling or binding or both based on the requirements. We determined the binding and execution time of image processing tasks and various routines of the Basic Linear Algebraic Subprogram (BLAS) using the proposed ILP for multiple combinations of weightage factors. Furthermore, a comparison analysis has been conducted to compare the latency and power dissipation of several benchmarks between the existing and proposed approaches. The experimental results demonstrate that the proposed method exhibits a substantial reduction in power consumption and latency compared to the existing method.